Rehabilitasi Sosial Korban Penyalahgunaan NAPZA di IPWL Karunia Insani Kabupaten Musi Rawas - Syahrio Marta Hila; Tamrin Bungsu (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2025)
Narcotics are classified as addictive substances because they lead to dependence, and they are classified as psychoactive substances because they affect brain function and alter the behavior of their users. The factors leading to drug abuse include the desire to try, the wish to appear different, and low self-confidence, ultimately resulting in addiction (a chronic brain disease of dependence). The purpose of establishing the Mandatory Report Recipient Institution (IPWL) is to fulfill the rights of drug addicts in accessing treatment or care through social rehabilitation. IPWL is required to continuously improve the quality of its services to become a strategic part of the solution to the problems faced by victims of drug abuse. The objective of this research is to analyze the implementation activities of social rehabilitation by the IPWL Karunia Insani in Musi Rawas Regency in addressing drug abuse issues. This study uses a qualitative method with descriptive analysis. Data collection techniques.The study was conducted using observation techniques, in-depth interviews, and documentation. The informants in this research consisted of 7 individuals, selected using Purposive Sampling technique. The informants included the Chairperson of IPWL Karunia Insani, Counselors, IPWL Staff, Clients, and the families of clients. The research findings indicate that IPWL Karunia Insani has carried out the stages of social rehabilitation quite well, including the initial acceptance stage (intake), early recovery stage (entry), main treatment stage (primary), resocialization stage (re-entry), and advanced coaching stage (aftercare) in efforts for Social Rehabilitation of Victims of Substance Abuse in Musi Rawas Regency.